Kingdoms and chiefdoms of southeastern Africa : oral traditions and history, 1400-1830 - Eldredge, Elizabeth A. (Rochester studies in African history and the diaspora, 2015)
"This study traces the social and political history of the peoples of early precolonial southeastern Africa, including the regions of modern KwaZulu-Natal, Swaziland, southern Mozambique from Maputo Bay southward, and Lesotho. The emergence in the early nineteenth century of well-known southern African kingdoms such as the AmaZulu, AmaSwazi, and BaSotho kingdoms was the culmination of centuries of sociopolitical developments, during which political control was consolidated in the ruling descent lines of small-scale chiefdoms. Providing the first comprehensive scholarly examination of recorded oral traditions from southeastern Africa, Eldredge's work chronicles the events and life stories propelling this consolidation and the advent of large-scale chiefdoms and kingdoms. Elizabeth A. Eldredge is an independent scholar and author of The Creation of the Zulu Kingdom, 1815-1828: War, Shaka, and the Consolidation of Power."